Distribution of mercury in the upper sediments from a polluted area (Ria de Aveiro, Portugal) - Ramalhosa, Elsa (2005)
This work reports levels of Hg, Fe and Mn and sulphides in the upper sediments of the Laranjo Basin, and examines the influence of these elements on the distribution of mercury.